Reforming Jim Crow : Southern politics and state in the age before Brown - Johnson, Kimberley S., 1966- (New York ; Oxford : Oxford University Press, 2010)
This text reshapes how we think about the origins of the civil rights era. The book paints a complex portrait of racial politics in the South in the first half of the 20th century and shows how the weaknesses in the Jim Crow system allowed reformers to lay some of the groundwork that would lead to the system's eventual collapse.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Brown, Oliver, -- 1918-1961.; African Americans -- Segregation; African Americans -- Civil rights; Civil rights -- Southern States -- History; Segregation in education -- Southern States -- History; Southern States -- Race relations; Southern States -- Politics and government